Utilização do coletor de uredósporos como indicador do momento da aplicação de fungicidas para controle da ferrugem asiática na cultura da soja - Sarto, Salvador Antonio (2012)
The aim of this work was to evaluate the best phenological stage of soybeans to make fungicide application for the control of Asian rust, based with or without uredospores the collector of spores. The experimental design used for the experiments was conducted in randomized blocks with four replications. The treatments were as follows: in the first experiment with the collector uredospore indicating the time of application in R1 (T - 1), R2 (T - 2), R3 (T - 3), R4 (T - 4), R5 ( T - 5), R6 (T - 6), T - 7 (no control) and T - 8 (full control) in the second experiment was applied fungicide at the same times of experiment 1, but without considering the collector as an indicator of the time of application of this product in soybeans. The fungicide was applied azoxystrobin + cyproconazole in a dose of 0.3 ha-1 in 200 L ha-1 spray volume, with the aid of pressurized with CO2 spray and equipped with tips of the fan type LD 110.02, the performance of the combined analysis indicated that for the agronomic characteristics, number of plants per area, number of pods per plant, number of seeds per pod and 100-grain mass was no significant difference (P <0.05) in function of use or non-collector as well as in relation to different application times of azoxystrobin + cyproconazole. However, in relation to productivity of grains observed that when the fungicide has been applied in the phenological stage R6 increased by approximately 22% compared to the applied R5, but not significantly different stages of R2 and R4. For incidence and severity of disease using collector indicated the time of fungicide application at phenological stage R5, providing less area under the curve of progress of the disease